O mitogenoma e o satelitoma de Astyanax altiparanae Garutti & Bristiski, 2000: considerações iniciais - Matheus Lewi Cruz Bonaccorsi de Campos (2020)
Among neotropical fish, the genus Astyanax is considered one of the most diverse and abundant. These fish are popularly known as “tetras” or “piabas” and despite being widely studied, their phylogenetic relationships are still uncertain, due to a complex taxonomy filled with cryptic species and species complex. For some decades, classical cytogenetics and molecular studies have provided valuable data on the chromosomal use of the genus, helping to identify species complexes and track their evolutionary histories. Following advances in genome sequencing technologies and computational biology, a new area has grown, Genomic Data Science, providing a wilderness of new tools and approaches for genetic, ecological and evolutionary studies in diverse organisms. In this dissertation, we explore some of these tools in the Astyanax altiparanae genome, which, unlike other species of the genus, has poor chromosomally diversity, where current cytogenetic markers can be less effective. With the genomic data obtained by Next-Generation Sequencing (NGS) and using a series of bioinformatics tools we aim to carry out the assembly of a complete mitogenome for A. altiparanae and analyze the satellite of this species. The mitogenome obtained was described and its functional annotation was made. We built a phylogeny from this mitogenome together with those of other characiforms available in the literature and explored the A. altiparanae satellite, where we discovered and classified 32 promising satellite DNA sequences for the species. Based on the results obtained, we conclude that phylogeny based on complete mitochondrial genomes makes the A. altiparane species the sister group of A. mexicanus and reinforces the idea of a paraphyletic condition for the genus. In addition, of the 32 sequences of repetitive elements identified, we suggest three as possible new cytogenetic markers for A. altiparanae and for the genus as a whole. Finally, we demonstrate that in silico approaches are a strong complement to the classic techniques of cytogenetics and FISH, being essential since, by addressing some of the limitations of these two techniques, they provide new starting points to better understand the genetic and chromosomal mechanisms behind the evolutionary patterns of Astyanax, thus helping in a more accurate reconstruction of the history of the genre.